One-step synthesis and AFM imaging of hydrophobic LDH monolayers. - Hu, G; Wang, N; O'Hare, D; Davis, J (2006)
Hydrophobic layered double hydroxide particles with a single layer structure have been successfully synthesised in a reverse microemulsion system; atomic force microscopy has proven a powerful tool for the study of these delicate nanoparticles.